Investigation of enzyme-sensitive lipid nanoparticles for delivery of siRNA to blood–brain barrier and glioma cells - Bruun J (Dove Medical Press, 2015)
Jonas Bruun,1 Trine B Larsen,1 Rasmus I Jølck,1 Rasmus Eliasen,1 René Holm,2 Torben Gjetting,1 Thomas L Andresen11Department of Micro- and Nanotechnology, Center for Nanomedicine and Theranostics, Technical University of Denmark, DTU Nanotech, Lyngby, Denmark; 2H Lundbeck A/S, Biologics and Pharmaceutical Science, Valby, DenmarkAbstract: Clinical applications of siRNA for treating disorders in the central nervous system require development of systemic stable, safe, and effective delivery vehicles that are able to cross the impermeable blood–brain barrier (BBB). Engineering nanocarriers with low cellular interaction during systemic circulation, but with high uptake in targeted cells, is a great challenge and is further complicated by the BBB. As a first step in obtaining such a delivery system, this study aims at designing a lipid nanoparticle (LNP) able to efficiently encapsulate siRNA by a combination of titratable cationic lipids. The targeted delivery is obtained through the design of a two-stage system where the first step is conjugation of angiopep to the surface of the LNP for targeting the low-density lipoprotein receptor-related protein-1 expressed on the BBB. Second, the positively charged LNPs are masked with a negatively charged PEGylated (poly(ethylene glycol)) cleavable lipopeptide, which contains a recognition sequence for matrix metalloproteinases (MMPs), a class of enzymes often expressed in the tumor microenvironment and inflammatory BBB conditions. Proteolytic cleavage induces PEG release, including the release of four glutamic acid residues, providing a charge switch that triggers a shift of the LNP charge from weakly negative to positive, thus favoring cellular endocytosis and release of siRNA for high silencing efficiency. This work describes the development of this two-stage nanocarrier-system and evaluates the performance in brain endothelial and glioblastoma cells with respect to uptake and gene silencing efficiency. The ability of activation by MMP-triggered dePEGylation and charge shift is demonstrated to substantially increase the uptake and the silencing efficiency of the LNPs.Keywords: matrix metalloproteinase, cleavable PEG-lipid, gene therapy, BBB, angiopep, nanocarrier